"I'm Here Because of Christ and Worshipping God …": Factors Influencing Religious Switching Among Ghanaian Charismatic/Neo-Pentecostal Christians. (December 2017) - Kpobi, Lily; Sarfo, Elizabeth Anokyewaa; Yendork, Joana Salifu
Many people like to identify as belonging to one church or another. Previous studies have explored the process of switching from one religious group to another, and this process has identified various factors that determine the likelihood and reasons for switching. Although this has been explored, little is known about the factors that influence switching among charismatic Christians in Ghana, and the potential implications of such switching on mental well-being. Our study therefore explored the reasons given by members of selected neo-Pentecostal/charismatic churches in Ghana for their decision to switch to these churches. The study was conducted in six neo-Pentecostal churches in Accra and Kumasi through the use of individual and focus group interviews as well as observations of church activities. A total of 86 respondents cited reasons such as geographic mobility, marriage, answers to prayer, as well as miracles and prophecies as their determining factors. These are discussed with emphasis on the potential implications for mental health such as psychological distress, blind faith, and individual agency.